MENGAJAR PEMBUATAN PERENCANAAN KOMUNIKASI PEMASARAN UNTUK MEMULAI BISNIS DI KALANGAN SMA - Pribadi, Muhammad Adi; Hardianto, Aldi (Jurnal Serina Abdimas, 2023)
Tarumanagara University sent a PKM team to Kristoforus 2 High School in West Jakarta to teach marketing communication planning in encouraging students to start business activities. Digital media makes it easier for them to carry out business activities. They have the opportunity to carry out business activities in high school because friendship at school makes it easier for them to introduce and sell their products. Marketing communication activities carried out by start-up businesses often ignore communication planning with consumers so that some entrepreneurs experience difficulties in business development. They need to understand the concept of marketing communications planning to succeed in business activities. The concept of marketing communication planning consists of problem definitions, business objectives, strategies, tactics, implementation, monitoring and evaluation. The speakers are Tarumanagara University lecturers and business practitioners so that they will teach the concepts of marketing communication planning according to their application. The hope of the Untar PKM team is that they try to do business activities after getting information. Universitas Tarumanagara mengirimkan tim PKM ke SMA Kristoforus 2 di Jakarta Barat untuk mengajarkan perencanaan komunikasi pemasaran dalam mendorong siswa siswi untuk memulai kegiatan bisnis sejak dibangku sekolah. Media digital memudahkan mereka untuk melakukan kegiatan bisnis sejak dini. Mereka memiliki peluang untuk melakukan kegiatan bisnis di SMA karena pertemanan di bangku sekolah mempermudah mereka dalam memperkenalkan dan menjual produknya. Kegiatan komunikasi pemasaran yang dilakukan oleh bisnis pemula sering mengabaikan perencanaan komunikasi dengan konsumen sehingga beberapa pengusaha mengalami kesulitan dalam pengembangan bisnis. Mereka perlu mengerti konsep perencanaan komunikasi pemasaran untuk berhasil dalam kegiatan bisnis. Konsep perencanaan komunikasi pemasaran terdiri dari Definisi masalah, Tujuan Bisnis, Strategi, Taktik, Implementasi, Monitoring, dan Evaluasi. Pemateri adalah dosen Universitas Tarumanagara dan praktisi bisnis sehingga ia akan mengajarkan konsep perencanaan komunikasi pemasaran yang sesuai dengan penerapannya. Harapan dari tim PKM Untar adalah mereka mencoba untuk kegiatan bisnis setelah mendapatkan information